Isolation and Identification Nanocalcium from Oyster Shell - Lia Handayani; Faisal Syahputra (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Oyster shell is one of the most potential solid waste as a source of natural calcium because it containsmore than 60% of CaCO3. The purposes of this research was to utilizing oyster shell into nanocalcium bycalcinations method, to characterise of nanocalcium. The oyster shell were milled in planetary ball millto fine a powder to uniform size of the sifted flour using a sieve of 200 mesh sieve. And then, Oyster shellpowder is calcinated in furnace with 900°C for 4 hours. the resulting material was denoted by nano-CaO. Theyield of nanocalcium obtained was 57.06%. Based on the analysis, nanocalcium contained calcium mineral(56.77%/100 g) and lead (15.9 ppm). The morphology of the sampel surface of the nanocalcium sampel wascomprises homogenous shape and size of particles with crystal form as vaterite and some aragonite.